Increased irrigation could mitigate future warming-induced maize yield losses in the Ogallala Aquifer - Lina Zhang; Guihua Bai; Steven R. Evett; Paul D. Colaizzi; Qingwu Xue; Gary Marek; Ramesh Dhungel; Haidong Zhao; Nenghan Wan; Xiaomao Lin (Communications Earth & Environment)
Abstract Irrigation is a fundamental practice for mitigating crop yield losses from drought and heat extremes. However, the extent to which irrigation moderates crop sensitivity to these stresses and the future quantity of irrigation required to maintain crop yields remain unclear. Here, we use a meta-analysis of maize field experiments across the Ogallala Aquifer to quantify how varying irrigation amounts influence yield sensitivity to heat and drought based on a panel regression model. We find that each 100 mm increase in irrigation reduces heat sensitivity of maize by 7.6%. By the 2050s, offsetting a projected 26% yield decline under a high-emission scenario, primarily driven by intensifying heat stress, would require a 67% increase in irrigation amounts. These findings provide key insights into the interplay between irrigation and climatic extremes, highlighting the urgent need for efficient irrigation strategies to balance crop yield and water resource sustainability.